Interactive Multimedia Based on A Problem Based Learning Model in Integrated Social Science Learning For Class Eight Junior High School - Anissi, Rinta Adestya; Darmansyah (JTP - Jurnal Teknologi Pendidikan, 2024)
Integrated social studies learning in junior high schools experiences problems, namely low student interest and learning outcomes. This is caused by students who are less active when studying. The aim of the research is to describe the process, validity, practicality and effectiveness of developing interactive multimedia based on the problem base learning (PBL) model in Integrated Social Sciences learning for class VIII SMP. This research uses the development and research (R&D) method with the ADDIE model. The data analysis technique in this research uses a Likert scale. Testing the validity of interactive multimedia includes material, media and language experts. The practicality test involved one Integrated Social Sciences teacher and 30 class VIII students at SMPN 22 Padang. The validity test results from material experts obtained a score of 3.5, media experts scored 3.6 and language experts scored 4 in the very valid category. The results of the practicality test by educators obtained a score of 3.9, and students scored 3.7 in the very practical category. The results of the effectiveness test obtained a very effective category because there were significant differences in student learning outcomes in using interactive multimedia.